Innovation in the platform of the Distance Education System in the Academic Division of Economic-Administrative Sciences of the Universidad Juárez Autónoma De Tabasco - et. al., Cristian Guadalupe Culebro Estrada, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The results of the analysis carried out on the platform of the distance modality of the bachelor's degree in marketing of the Universidad Juárez Autónoma de Tabasco are shown, in order to identify the innovation opportunities presented by the platform of the distance education system, for what which was carried out an investigation focused on the students who use this technological tool; Applying surveys to the students of the degree in marketing and analyzing the results obtained, it is concluded that the design of the page can be improved in order to make it more accessible to higher education students.